Target balances and the German financial account in light of the European balance-of-payments crisis - Hans-Werner Sinn; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2012)
As shown in Sinn and Wollmershäuser (2012a), during the European balance-of-payments crisis, inter-governmental credit and Target credit granted by core-country central banks have replaced private international capital flows in financing the crisis countries' current account deficits, and even compensated for outright capital flight. This article offers a closer look at the components of this reversal of capital flows for the case of Germany. Its main finding is that most of the reversal materialized in the decline in foreign claims of German commercial banks. The inflow of foreign flight capital into Germany is small by comparison, with purchases of German government bonds increasing substantially, in particular by Spanish and Irish investors. Some foreign capital even left Germany. In net terms, over the years 2008, 2009 and 2011 foreigners withdrew credit they had previously provided to German financial institutions. However, in 2012, foreign credit flows to German financial institutions surged, while the flow of credit redemptions paid to German financial institutions came to a halt.
Keywords: E50; E58; E63; F32; F34; 330; monetary union; balance of payments; financial account; capital flight; Target; Internationaler Zahlungsverkehr; Kapitalbilanz; Deutschland; Zahlungsbilanzungleichgewicht; Kapitalflucht; Europäische Wirtschafts- und Währungsunion; Eurozone